Follow-up study of the treatment outcomes at a psychiatric trauma clinic for refugees - Buhmann, Cæcilie; Mortensen, Erik Lykke; Nordentoft, Merete; Ryberg, Jasmina; Ekstrøm, Morten (Torture Journal, 2018)
Purpose: To describe change in mental health after treatment with antidepressants and trauma-focused cognitive behavioral therapy. Methods: Patients receiving treatment at the Psychiatric Trauma Clinic for Refugees in Copenhagen completed self-ratings of level of functioning, quality of life, and symptoms of PTSD, depression, and anxiety before and after treatment. Changes in mental state and predictors of change were evaluated in a sample that all received well-described and comparable treatment. Results: 85 patients with PTSD or depression were included in the analysis. Significant improvement and effect size were observed on all rating scales (p-value <0.01 and Cohen’s d 45-0.68). Correlation analysis showed no association between severity of symptoms at baseline and the observed change. Conclusion: Despite methodological limitations, the finding of a significant improvement on all rating scales is important considering that previous follow-up studies of comparable patient populations have not found significant change in the patients’ condition after treatment.